Effectiveness of different treatment regimens of enhanced external counterpulsation in patients with stable coronary artery disease complicated by heart failure - A. S. Lishuta; O. A. Slepova; N. A. Nikolaeva; N. V. Khabarova; E. V. Privalova; Yu. N. Belenkov (Рациональная фармакотерапия в кардиологии, 2024)
Aim. To study the effect of various therapy regimens with enhanced external counterpulsation (EECP) on exercise tolerance, quality of life, indices of structural and functional state of cardiovascular system in patients with stable coronary artery disease (CAD) complicated by chronic heart failure (CHF).Material and methods. The study included patients with stable CAD complicated by CHF with reduced and intermediate left ventricular ejection fraction (LVEF) from the randomized EXCEL trial (NCT05913778; n=120) and additionally patients with similar inclusion and exclusion criteria (n=90) who were randomized into groups with different EECP treatment regimens for 12 months: Group 1 (n=40): course of 35 hour-long procedures; Group 2 (n=40): course of 35 hourlong procedures every 6 months; Group 3 (n=30): course of 20 hour-long procedures then constantly 1 hour per week; Group 4 (n=30): constantly 2 hours per week; Group 5 (n=30): course of 20 hour-long procedures then constantly 2 hours per week; Group 0 (placebo ; n=40): course of 35 hour-long procedures with compression pressure 80 mm Hg. All patients at baseline and after 12 months were assessed for clinical status, quality of life (MLHFQ, SF-36), NT-proBNP levels, LVEF, as well as exercise tolerance (6-minute walk test; 6MWT) initially, after 3, 6, 9 and 12 months. Correlation analysis and risk assessment of adverse events (combined endpoint — combination of cases of adverse cardiovascular events, deaths, hospitalizations for CHF, new-onset of atrial fibrillation, diabetes, decreased renal function) was performed.Results. Treatment effectiveness had positive correlation with EECP duration (r(S)=0,670; p<0,001) and treatment regimen (r(S)=0,620; p<0,001). The maximum effect (changes in NT-proBNP levels, LVEF, clinical status, quality of life) was noted in the combined and constant regimen groups (5, 4, 2). The increase of 6WMTdistance was 6,6% in group 0, 24,9% in group 1, 44,5% in group 2, 31,8% in group 3, 49,1% in group 4, 58,6% in group 5. The proportion of patients with an increase in 6WMT-distance >20% after 12 months was 7,7%, 72,5%, 97,5%, 76,7%, 90%, 100%, respectively. Cumulative event-free survival was highest in groups 5, 4, and 2 (0,97, 0,93, and 0,86, respectively), and the risk of developing combined endpoint in these groups was minimal (0,035, 0,075, and 0,150, respectively).Conclusion. The effect of EECP treatment in patients with coronary artery disease complicated by CHF depended on the EECP hours and regimen. Alternative EECP regimens (with more treatments spread evenly over the year) in addition to optimal medical therapy may improve the management of these patients.